Induksi Tetraploid Tunas Pucuk Jeruk Siam Simadu (Citrus nobilis Lour) Menggunakan Kolkisin secara In Vitro - Yulianti, Fitri; Purwito, Agus; Husni, Ali; Dinarti, Diny (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2015)
Seedless fruit is one of the criteria (necessary) to improve the quality of Simadu tangerine. The most effective method to obtain seedless triploid cultivars is hybridisation between tetraploid and diploid parents. Simadu tangerine is a diploid plant. Tetraploid Simadu tangerine can be obtained with doubling chromosome using colchicines.The aim of this research was to obtain tetraploid Simadu tangerine shoot which would serve as parent to produced seedless Simadu tangerine. Shoot-tips of Simadu tangerine without leaves were treated with colchicines at four different concentrations (0, 0.1, 0.2, and 0.3%) for 3 hours. The results showed that the high concentration of 0.3% reduced survival rate. The colchicine treatments reduced growth of shoot-tip of Simadu Tangerine.The leaves of colchicines treated shoots were thicker than control. Leaves from control (0% colchicine) and 0.1% colchicine treated shoots had 8.67 and 18.25 chloroplast per pair of guard cells. Compared to those of control, leaves with 0.1% colchicine had lower stomatal density, and larger stomatal size. It appeared that 0.1% colchicine treatment resulted in tetraploid Simadu Tangerine Shoot.Keywords:chloroplasts, doubling chromosomes, stomatal size, stomatal density